Preparation of TiO2 Superhydrophobic Composite Coating and Studies on Corrosion Resistance - Zhou, Chaogang; Chen, Qiya; Chen, Qinggong; Yin, Huawei; Wang, Shuhuan; Hu, Chuanbo (Frontiers in Chemistry, 2022)
The superhydrophobic coatings with excellent performance are prepared on the brass substrate to improve its application limitations in real production. In this paper, the superhydrophobicity was obtained by the modification of TiO2 nanoparticles, and the FAS/STA-TiO2 superhydrophobic coating of the composite structure was obtained by modification of 1H, 1H, 2H, 2H-perfluoroquine trimethyl silane (FAS). By scanning electron microscopes (SEM), X-ray spectrometers (EDS) and Fourier infrared spectrometers (FTIR), the surface morphology、chemical composition and functional group structure of the samples were analyzed in turn. The surface wettability, self-cleaning, adhension and corrosion resistance of the coating were investigated by using contact angle measuring instrument, chalk dust containment, tape stripping and Tafel polarization curve. Experiments show that the water contact angle of the FAS modified STA-TiO2 coating reaches 161.3° and the sliding angle is close to 1.2°. In the tape peeling experiment, FAS/STA-TiO2 coating also shows good mechanical stability. Moreover, the FAS/STA-TiO2 coating has a corrosion current density as low as 8.41 × 10-7A/cm2 in a 3.5% NaCl solution to achieve better protection of the brass substrate. It is also not difficult to see that FAS/STA-TiO2 coating can not only improve the corrosion resistance of brass substrates, but also can be applied to other metal substrates.